2022
DOI: 10.3389/fpubh.2022.937887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of needle-stick injury among nursing students: A systematic review and meta-analysis

Abstract: IntroductionNeedle-stick injuries (NSI) are a serious threat to the health of healthcare workers, nurses, and nursing students, as they can expose them to infectious diseases. Different prevalence rates have been reported for this type of injury in different studies worldwide. Therefore, this study aimedto estimate the pooled prevalence of NSI among nursing students.MethodsThis study was conducted by searching for articles in Web of Science, PubMed, Scopus, Embase, and Google Scholar without time limitation us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…These percentages are lower than different studies, such as Germany (21.4%) ( 36 ) and Taiwan (18.2%) ( 37 ). A recent systematic review and meta-analysis showed that the prevalence of NSI among nursing students in Asia countries was higher than in Europe (39.7%) ( 38 ). Failure to recap the needles was reported as a common cause of NSIs, similar to several studies ( 6 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These percentages are lower than different studies, such as Germany (21.4%) ( 36 ) and Taiwan (18.2%) ( 37 ). A recent systematic review and meta-analysis showed that the prevalence of NSI among nursing students in Asia countries was higher than in Europe (39.7%) ( 38 ). Failure to recap the needles was reported as a common cause of NSIs, similar to several studies ( 6 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, many students did not fill out an incident report because they were worried and feared being blamed. Under-reporting NSI is a major clinical challenge that may have undermined the validity of existing data regarding this issue ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The total score for the AHRQ ranges from 8 to 11 points for high quality, 4 to 7 points for medium quality, and 0 to 3 points for low quality. The Newcastle‐Ottawa Scale (NOS) was employed to appraise the methodological quality of the included cohort studies (Xu et al., 2022). According to the scoring criteria of this table, the overall rating is based on the cut‐off values of 1–3, 4–6, and 7–9, representing high, moderate, and low risk of bias, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The total score for the AHRQ ranges from 8 to 11 points for high quality, 4 to 7 points for medium quality, and 0 to 3 points for low quality. The Newcastle-Ottawa Scale (NOS) was employed to appraise the methodological quality of the included cohort studies (Xu et al, 2022).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Highest NSI prevalence in nursing staff has also been reflected in other studies ( 7 , 8 ). Nursing students have been found to experience NSI with one meta-analysis revealing an incidence of 35% among nursing students across 32 studies ( 9 ).…”
Section: Dangers Of Needlestick Injuriesmentioning
confidence: 99%